Cation-tunable flower-like (NixFe1−x)2P@graphitized carbon films as ultra-stable electrocatalysts for overall water splitting in alkaline media. Issue 35 (23rd August 2019) - Zhao, Hongyang; Wang, Yanwei; Fang, Ling; Fu, Weiwei; Yang, Xiaohui; You, Shili; Luo, Ping; Zhang, Huijuan; Wang, Yu
Abstract : Electrocatalytic water splitting is a promising strategy for green and renewable energy development by transforming electrical energy into hydrogen energy. Abstract : Electrocatalytic water splitting is a promising strategy for green and renewable energy development by transforming electrical energy into hydrogen energy. Herein, we report a series of flower-like electrocatalysts with cation-tunable (Ni x Fe1− x )2 P nanoparticles encapsulated by porous graphitized carbon films (GCs) via the combination of morphology control and component adjustment. By progressively tailoring the atomic ratios of Ni/Fe, the electronic structure and electrocatalytic activities of (Ni x Fe1− x )2 P can be intriguingly modified to achieve versatile catalytic behavior for both the HER and the OER. DFT calculations also validate that the (Ni x Fe1− x )2 P with an optimal atomic ratio of Ni/Fe can support the |Δ G H* | to be close to the optimum and decrease the adsorption energy for water, which can boost the water splitting. Meanwhile, anchoring the adjustable (Ni x Fe1− x )2 P nanoparticles into GC interlayers can endow these composites with more available active sites, excellent conductivity and enhanced stability. In fact, the combined synergistic effect of cation-tuned (Ni x Fe1− x )2 P nanoparticles and porous conductive GCs is the reason that these composites exhibit enhanced electrocatalytic activities, as illustrated by a low overpotential of 206 mV at j = 10 mA cm −2 (256 mV at j = 50 mA cm −2 ) for the OER. Meanwhile, the bifunctional (Ni0.75 Fe0.25 )2 P@GCs, as both the cathode and anode of an electrolyzer, effectuates an ultra-small cell potential of 1.541 V at j = 10 mA cm −2 (1.573 V at j = 20 mA cm −2 ) for 30 h during electrolysis of water, rivaling commercial IrO2 and Pt/C catalysts. More importantly, this work can provide a way of fabricating cost-saving, component-tunable and high-efficiency bimetallic electrocatalysts for water splitting.